Study of biomarkers to determine severity and lung damages in COVID-19 patients - Alfian Nur Rosyid; Arina Dery Puspitasari; Wiwin Is Effendy; Herley Windo Setiawan; Arief Bakhtiar; Isnin Anang Marhana; Anggraini Dwi Sensusiati; Jusak Nugraha; Muhammad Amin (Journal of Infection in Developing Countries)
Introduction: Identifying inflammation and lung damage markers is crucial in reducing morbidity and mortality of coronavirus disease 2019 (COVID-19). This study aimed to examine the validity and reliability of severity and post-infection lung damage and analyse their relationship.